Reconstructing the Economic Landscape of Ekaterinburg City in 1914 Based on the Telephone Network - Dmitry Sergeevich Bakharev; Aleksandr Vladimirovich Bobitsky (Известия Уральского федерального университета. Серия 2: Гуманитарные науки, 2023)
This paper reconstructs Ekaterinburg’s economic landscape in 1914. The research is based on the 1910 city map and quantitative data from the 1914 city phonebook and relies on the space syntax method. During the study, the authors created a database including 390 local companies’ phone numbers before World War I classified in accordance with the Fisher-Clark economic sector model (primary sector — extraction of raw materials, secondary — manufacturing, tertiary — service industries, quaternary — finances and information services, quinary sector — administration, education, medicine, sciences, etc.). The research demonstrates that there were just a couple of primary sector businesses in Ekaterinburg in the early twentieth century. Most secondary sector plants and factories had been moved outside of the city, while the others were evenly distributed following the environmental regulations and proximity to labour force. Tertiary sector firms dominated in the western part of the city and formed a commercial district around Market Square. The quaternary sector companies had almost the same location, spreading further to the northwest. Quinary sector organisations were dispersed all over the city with a notable concentration in the center and north-western part. The reconstruction of the Ekaterinburg economic landscape reveals that its centre occupied the area around the dam that locked the Iset River running through the city and spread towards the west and north-west part in the early twentieth century forming the city’s future business district.